Template morphology and serial invariants : compositional procedures in Stravinsky's late sketch collections, 1958-66 - Caulfield, Fergus G. (Trinity College (Dublin, Ireland). Department of Music, 2001)
This thesis employs unpublished holograph sketch and draft material now in the possession of the Paul Sacher Stiflung, Basel, to investigate how serial deployment and the exploitation of row properties in the later works of Igor Stravinsky operate within the context of the composer’s ongoing modus operandi. In particular, it examines the composer’s predilection for generating templates, most frequently in the form of condensed ‘capsule’ sketches, which act as referential models for a number of musical parameters throughout the compositional process.
Keywords: Music, Ph.D.; Ph.D. Trinity College Dublin